INFLUENCE OF OSCILLATORY IMPACT ON MOVEMENT IN LIQUID AND GRINDING OF WOOD PULP USED FOR PACKAGING PRODUCTION - I. I. Karpunin (Наука и техника)
The paper investigates an influence of oscillatory impacts on wood pulp grinding which is used for packaging production.It has been established that plate oscillatory impact promotes better quality of the obtained paper sheet made of grind plant fiber.